SISTEM TANAM HIDROPONIK SAYUR BAYAM MERAH (Amaranthus gangeticus) DENGAN MENGGUNAKAN LIMBAH CAIR TAHU SEBAGAI NUTRISI PERTUMBUHAN - Anita Restu Puji Raharjeng; Awalul Fatiqin; Riri Novita Sunarti (Jurnal Biosilampari : Jurnal Biologi, 2018)
The aims of this research is to know the effect of liquid wastes on vegetative growth of red spinach plants. This research used Factorial Random Design (RAL). Objeks in this research are nutrient solution (L) and planting medium (M). The data was analyzed using two way ANOVA. The treatment in this research is nutrient solution (L) and planting medium (M). There are 2 types of nutrients used, the aquadest and the tofu liquid waste. There are 2 types of medium used, the cocopeat media and sand media. From result of research it is known that, at treatment L1M1 which is treatment with tofu liquid waste on cocopeat planting medium technique obtained high yield of planting with average 7,70 cm. Likewise on the observation of the number of leaves on L1M1 treatment also obtained an average yield of 4.00 pieces. Similarly, at the roots of red spinach plants obtained the highest average, namely the treatment of L1M1 with an average root length of 23.75 cm. Conclusion the use of tofu liquid waste as an additional nutrient for the growth of red spinach vegetable plants has an effect on the vegetative growth of red spinach plants.